Additive manufacturing of carbon steels by materials extrusion of oxide precursors and hydrogen reduction - Collin Stiers; Katie Koube; Ethan Sinclair; Hyoungjun Sim; Elias Winterscheidt; Josh Kacher (Additive Manufacturing Letters, 2023)
A hydrogen reduction-based method for additive manufacturing of carbon steels from low cost and stable oxide powders is presented. This method uses materials extrusion processes to extrude inks composed of oxide powders, plastic binders, and solvents. Oxide powders are synthesized into viscous inks and extruded under ambient conditions into three-dimensional architectures. The three-dimensional printed green bodies are reduced at elevated temperatures in hydrogen-rich environments to burn off the polymer binder and reduce the oxide powders, yielding metal alloys with controlled compositions. While this approach has been demonstrated in previous publications for various alloys, the addition of carbon, an important element in most industrial steels, has been a persistent challenge. This paper demonstrates an approach to introduce carbon during the reduction process, resulting in through-thickness carburization of the final parts.